Tolerância de genótipos de gergelim ao estresse hídrico em cultivo com biofertilizante - Ribeiro, Victor Herbert de Alcântara (2019)
The sesame (Sesamum indicum L.), an oleaginous oil belonging to the Pedaliaceae family, is a crop with a high potential for growth in the national and world market due to the quality of its seeds and oil. The species is also characterized by its tolerance to drought, adaptation to different types of soil, with good values of productivity and use of oil in various activities, in the food and chemical industries. In the history of cultivation in regions of northeastern Brazil, its particularity stands out to produce even in periods with low rainfall, and studies should be intensified based on this characteristic. Depending on the soil fertility level of the region, research with biofertilizer sources and its effect on the production of this oilseed should also be studied. The objective of this research was to evaluate the degree of tolerance to water stress of sesame genotypes ('BRS Seda', 'BRS Morena' and 'BRS Anahi') with biofertilizer applications in different phenological phases. The experiment was carried out in a greenhouse at EMBRAPA Algodão, in Campina Grande, consisting of the use or not of a biofertilizer, three cultivars and three levels of water management of the plants. The factors were arranged in a randomized block design, with a factorial scheme 2 x 3 x 3 (biofertilizer x cultivars x water management) with five replications, totaling 90 plants. Growth variables were evaluated: Plant height, stem diameter, number of leaves; Physiological variables: Gaseous exchanges and Fluorescence of chlorophyll a '; and Production variables: Number of fruits per plant, Seed Mass, Thousand seed mass, Number of seeds (capsule). The data obtained were evaluated by the 'F' test, with Tukey's test comparisons (p <0.05) and t-test for biofertilizer application. The increase of the irrigation blade positively affected the height of the sesame plant, stem diameter, number of fruits and number of leaves. At 60 and 90 DAE an increase in stem diameter was observed when the biofertilizer was applied. The increase of the irrigation slabs did not interfere in the internal CO2 concentration, but the biofertilizer application was statistically different in the 70% lamina. For seed mass, the cultivars Anahi and BRS Seda were positively influenced by the use of biofertilizer when submitted to slides of irrigation of 70 and 100% of the water replenishment. For the number of seeds, the cultivars BRS Seda and Morena presented higher averages in the seed production when compared to Anahi, among the cultivars, the one that produced a greater number of fruits was BRS Seda.